2016
DOI: 10.1177/2332858416679374
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Equity in the Distribution of Teachers With Special Education Credentials

Abstract: the annual shortage of special education teachers (SETs) across the United States poses staffing challenges for local school districts (U.S. Department of Education, 2015a) and the education of nearly 6.5 million children with disabilities (U.S. Department of Education, 2015b). However, efforts to improve the supply of SETs often overlook key concerns about the diversity and distribution of SETs across schools. In special education under the Individuals with Disabilities Education Act (IDEA; 2004), students of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Although this 20% discrepancy was not statistically significant, it suggests an important and unfortunate disparity in the allocation of highly qualified SETs, disadvantaging students of color. This finding is consistent with those of previous researchers who have found that the distribution of teachers with special education credentials is driven by geography, school poverty, student achievement, and racial composition (Cooc & Yang, 2016; Dee & Goldhaber, 2017; Mason-Williams, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Although this 20% discrepancy was not statistically significant, it suggests an important and unfortunate disparity in the allocation of highly qualified SETs, disadvantaging students of color. This finding is consistent with those of previous researchers who have found that the distribution of teachers with special education credentials is driven by geography, school poverty, student achievement, and racial composition (Cooc & Yang, 2016; Dee & Goldhaber, 2017; Mason-Williams, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Historically, supplying all schools and classrooms with fully prepared, qualified special education teachers has been a considerable challenge. Ample evidence suggests critical shortages, especially in schools serving students from low-income areas, schools primarily serving students of color, and in rural schools (Croc & Yang, 2016;Mason-Williams, 2015;Sindelar et al, 2018). Moreover, preparation appears to matter for retention and avoiding burnout, indicating how essential it may be to maintain clinical practice activities so novice special educators feel adequately prepared for their role (Billingsley & Bettini, 2019;Ondrasek et al, 2020).…”
Section: Challenges Created or Exacerbated By Covid-19mentioning
confidence: 99%
“…The authors concluded, “recruiting and retaining culturally and linguistically diverse teachers in special education remains a challenge to the whole of education, particularly to special education teacher education” (p. 299). This statement remains true today, but recent findings indicate that, in the past decade, progress has been made (Cooc & Yang, 2016). In an analysis of California data sets between 1997 and 2014, Cooc and Yang found a substantial rate of increase of teachers of color in special education in comparison with their general education counterparts.…”
Section: Introductionmentioning
confidence: 95%
“…State and federal efforts to recruit racially and ethnically diverse teachers have begun to bear some fruits and “minorities have entered teaching at higher rates than whites in recent decades” (Ingersoll et al, 2014, p. 18). This is evident within special education, for example, in California where the proportion of teachers of color with special education credentials increased at 2 times the rate compared with those in general education (Cooc & Yang, 2016). In this study, we turn to intersectionality as a lens for conceptualizing diversity and equity (Collins, 1990; Crenshaw, 1989) to examine how markers of difference —or minoritized categories of race, gender identity, linguistic origin, age, socioeconomic status (SES), class, ethnicity, dis/ability, religion, sexuality, nationality, or citizenship—simultaneously intersect within the P-12 school context.…”
Section: Introductionmentioning
confidence: 99%